Audio Visual Poster Media Based on Scientific Approach to Water Cycle Material in Fifth Grade Elementary School - Tarayani, Ni Putu Yuyun Verginia; Rati, Ni Wayan (Universitas Pendidikan Ganesha, 2024)
Currently, learning is more centered on teacher activities. This is because there is no creative and innovative learning media so that can affect student learning outcomes to decline. The purpose of this study is to produce audio-visual poster media based on a scientific approach to water cycle material in elementary school grade V science learning to improve student interest and learning outcomes. The development model used in this study is the ADDIE. The subject of the product trial in this development research is the subject at the expert review stage carried out by two material experts. The types of data used in this study are qualitative data and quantitative data. The results of the study are (1) audio-visual poster media based on a scientific approach. (2) the validity of audio-visual poster media based on a scientific approach by obtaining an average score from material experts, learning media experts, and learning design experts of 4.50 with a very valid category. (3) the practicality analysis filled in by the teacher obtained an average score of 4.81 with a very valid category. (4) the practicality analysis filled in by students individually and in small groups obtained an average score of 4.59 and 4.56 with a very valid category. Based on this, it can be concluded that the audio-visual poster media based on a scientific approach to the water cycle material in grade V of elementary school is declared valid with a very good qualification.